Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

Section 10.1 Answers

  • Page ID
    30064
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    1. \(\begin{array}{l}{Q'_{1}=2-\frac{1}{10}Q_{1}+\frac{1}{25}Q_{2}}\\{Q'_{2}=6+\frac{3}{50}Q_{1}-\frac{1}{20}Q_{2}}\end{array}\)

    2. \(\begin{array}{l}{Q'_{1}=12-\frac{5}{100+2t}Q_{1}+\frac{1}{100+3t}Q_{2}}\\{Q'_{2}=5+\frac{1}{50+t}Q_{1}-\frac{4}{100+3t}Q_{2}}\end{array}\)

    3. \(\begin{array}{l}{m_{1}y_{1}''=-(c_{1}+c_{2})y'_{1}+c_{2}y'_{2}-(k_{1}+k_{2})y_{1}+k_{2}y_{2}+F_{1}}\\{m_{2}y_{2}''=(c_{2}-c_{3})y'_{1}-(c_{2}+c_{3})y'_{2}+c_{3}y'_{3}+(k_{2}-k_{3})y_{1}-(k_{2}+k_{3})y_{2}+k_{3}y_{3}+F_{2}}\\{m_{3}y_{3}''=c_{3}y'_{1}+c_{3}y'_{2}-c_{3}y'_{3}+k_{3}y_{1}+k_{3}y_{2}-k_{3}y_{3}+F_{3}}\end{array}\)

    4. \(x''=-\frac{\alpha}{m}x'+\frac{gR^{2}x}{(x^{2}+y^{2}+x^{2})^{3/2}}\qquad y''=-\frac{\alpha}{m}y'+\frac{gR^{2}y}{(x^{2}+y^{2}+x^{2})^{3/2}}\qquad z''=-\frac{\alpha}{m}z'+\frac{gR^{2}z}{(x^{2}+y^{2}+z^{2})^{3/2}}\)

    5. 

    1. \(\begin{array}{l}{x'_{1}=x_{2}}\\{x'_{2}=x_{3}}\\{x'_{3}=f(t,x_{1},y_{1},y_{2})}\\{y'_{1}=y_{2}}\\{y'_{2}=g(t,y_{1},y_{2})}\end{array}\)
       
    2. \(\begin{array}{l}{u'_{1}=f(t,u_{1},v_{1},v_{2},w_{2})}\\{v'_{1}=v_{2}}\\{v'_{2}=g(t,u_{1},v_{1},v_{2},w_{1})}\\{w'_{1}=w_{2}}\\{w'_{2}=h(t,u_{1},v_{1},v_{2},w_{1},w_{2})}\end{array}\)
       
    3. \(\begin{array}{l}{y'_{1}=y_{2}}\\{y'_{2}=y_{3}}\\{y'_{3}=f(t,y_{1},y_{2},y_{3})}\end{array}\)

    4. \(\begin{array}{l}{y'_{1}=y_{2}}\\{y'_{2}=y_{3}}\\{y'_{3}=y_{4}}\\{y'_{4}=f(t,y_{1})}\end{array}\)
       
    5. \(\begin{array}{l}{x'_{1}=x_{2}}\\{x'_{2}=f(t,x_{1},y_{1})}\\{y'_{1}=y_{2}}\\{y'_{2}=g(t,x_{1},y_{1})}\end{array}\)

    6. \(\begin{array}{ll}{x'=x_{1}}&{x'_{1}=-\frac{gR^{2}x}{(x^{2}+y^{2}+x^{2})^{3/2}}}\\{y'=y_{1}}&{y'_{1}=-\frac{gR^{2}y}{(x^{2}+y^{2}+x^{2})^{3/2}}}\\{z'=z_{1}}&{z'_{1}=-\frac{gR^{2}z}{(x^{2}+y^{2}+z^{2})^{3/2}}}\end{array}\)